Neighborhood story. 1 - Yazawa, Ai, 1967- (Shojo beat manga., 2023)
"Welcome to Happy Berry! No, this isn't a fruit stand, but the label dreamed up by aspiring fashion designer Mikako Koda. In her quest to make a name for herself in the fashion world, Mikako enters Yazawa Arts Academy, a prestigious art school, alongside her strictly platonic childhood friend Tsutomu. But there's one problem--Tsutomu's uncanny resemblance to a rock star skyrockets him to popularity and leads him to date the prettiest girl in school. Now Mikako can't help but wonder if what she feels is jealousy. Peppy and creative teenager Mikako wants nothing more than to make it as a fashion designer. But when she enters art school alongside her lifelong friend Tsutomu, she finds herself distracted by his sudden popularity and subsequent love life. Despite her feelings, Mikako forms a club with Tsutomu and her friends to sell their creations at a local flea market. While the group is out scouting the flea market, however, discord arises between members in the group and what begins as an exciting day quickly turns sour."--Amazon.